Post memory and cinematic affect in The Midwife. Issue 1 (1st January 2017) - Hiltunen, Kaisa; Sääskilahti, Nina
ABSTRACT: The Second World War has proved a rich source of inspiration for fiction films worldwide. The Finnish fiction film The Midwife ( Kätilö, Antti J. Jokinen, 2015) is aimed at an international audience with a story that takes place in the context of the Lapland War in Finland in 1944. The film tells of a romantic relationship between a local woman and a member of the German army, in a highly affective manner. This article argues that the film downplays elements that might have interested the national, or local, audience, and that it privileges affect over knowledge. To bring out the film's transnational character, the article begins by analysing it in the context of national, or local, and global influences and argues that the film's decontextualised, deterritorialised, and denationalised nature can be a result of its desire to appeal to a wide audience; yet a set of tensions and paradoxes are identified that bring out the complexities of the local–global nexus. The article goes on to ask whether the affectivity emphasised in The Midwife could have been a means to produce a story that communicates across borders. The article also explores whether affectivity can be a way to create a meaningful connection to the past in the current era of post memory (Aleida Assmann). Analysis of the film's aesthetic and narrative devices is combined with cultural analysis of the contemporary memory and media culture and its global flows.